Language learners as ethnographers - Roberts, Celia, 1947- (Modern languages in practice, 2001)
"This book describes a new approach to teaching and learning cultural studies. Borrowing the idea of ethnography from anthropologists, it argues that language students can be taught methods for investigating the cultural and social patterns of interaction and the values and beliefs that account for them. Doing an ethnographic study while resident abroad immerses students in the life of particular groups, providing an intellectual challenge and the opportunity for intense intercultural encounters."--Jacket